The 2 × 2 model of perfectionism and youth sport participation: A mixed-methods approach. (May 2018) - Mallinson-Howard, S.H.; Knight, C.J.; Hill, A.P.; Hall, H.K.
Abstract: Objectives: Research demonstrates that four subtypes of perfectionism from the 2 × 2 model are associated with different youth sport experiences. This study provided the first exploration of the experiences of youth sport participants exhibiting different subtypes of perfectionism using mixed-methods. Design: A two-stage, mixed-methods, approach was adopted (quantitative identification then qualitative data collection). Method: In stage one (quantitative identification), 192 females enrolled in school- or community-based sport groups ( M age = 13.91; SD = .90; range 12–16 years) completed a domain-specific perfectionism instrument (Sport-MPS-2) to identify participants prototypical of the four subtypes of perfectionism. In stage two (qualitative data collection), 19 prototypical participants ( M age = 13.74; SD = .65; range 13–15 years) described their experiences of their youth sport involvement. One focus group ( n = 4 to 5 per group) and one follow-up individual, semi-structured, interview ( n = 4 in total) per subtype were conducted. Results: Thematic analysis revealed that the meaning youth sport participants gave to their sport involvement (i.e., goals, values, and purposes) and the features of the social-environment they perceived to be important differed between the four subtypes of perfectionism. For the "pure PSP" and "mixed perfectionism" subtypes, sport was a time to shine and experience success. For the "non-perfectionism" and "pure ECP" subtypes, sport was a place to make friends and belong. Participants from all four subtypes described the importance of the coach and peers, with some groups identifying different preferred roles for the coach in terms of type and amount of involvement. Conclusions: Youth sport participants exhibiting different subtypes of perfectionism vary in their experiences of youth sport. Practitioners working with young people in sport should consider these differences so to better understand and improve youth sport experiences. Highlights: The experiences of perfectionistic youth sport participants were explored. Both quantitative and qualitative research methods were employed. Sport experiences differed considerably dependent upon the subtype of perfectionism. Novel insights were gained into the meaning of sport for perfectionistic youths. Coaches/peers appeared vital in shaping perfectionistic youths' sport experiences.